Impact of Educational Youtube Videos on EFL Students' Speaking Fluency in Indonesian Secondary Schools - Anand, Raju; Syahid, Abdul; Widiastuty, Hesty (IKIP Siliwangi, 2025)
Improving speaking fluency remains a challenge for EFL students in secondary schools, highlighting the need for innovative teaching methods. Fluency involves expressing oneself naturally, without frequent pauses or hesitations, and participating in conversations confidently. Educational YouTube videos, designed to teach or share knowledge, engage viewers through both visual and audio elements, making them effective learning tools. This study explored the use of YouTube videos to enhance speaking fluency among EFL students. A quasi-experimental design was employed, with 65 participants divided into an experimental group, using YouTube videos, and a control group, using educational podcasts, over the course of one month. Results indicated a significant improvement in speaking fluency, with the experimental group scoring 655 compared to the control group's 455. The findings suggest that using YouTube videos can be a more effective tool for improving speaking fluency than traditional methods. This study provides a reference for future research in the field, encouraging further exploration of innovative approaches to language teaching and fluency enhancement.